The Impact Of Entrepreneurship Programs And Islamic Educational Values On The Creativity Of Santri At Anwarul Haromain Islamic Boarding School, Trenggalek - Sholichah, Chamidatus; Hosna, Rofiatul (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study investigates the influence of entrepreneurship programs and Islamic educational values on the creativity of female students (santri) at Anwarul Haromain Islamic Boarding School in Trenggalek. In an era that demands both spiritual depth and economic resilience, pesantren are increasingly integrating entrepreneurship education to equip students with practical skills rooted in Islamic ethics. This research aimed to assess the individual and combined effects of entrepreneurship programs and Islamic educational values on student creativity. Using a quantitative ex post facto design, data were collected from 59 randomly selected students via questionnaires and institutional documentation. While descriptive results show generally positive student perceptions toward both entrepreneurship initiatives and Islamic educational values, statistical analysis revealed that neither factor had a significant individual effect on creativity. However, when combined, these variables showed a meaningful joint influence, explaining a modest proportion of the variance in students’ creative development. This suggests that integration, rather than isolation, of ethical and practical education may better foster creative competencies. The study highlights the importance of holistic approaches that blend moral and entrepreneurial learning. Additionally, it introduces the Islamic Creativity Triad (ICT) as a conceptual model for integrating Islamic epistemology with creativity and entrepreneurship education. While promising, the model remains theoretical and requires further empirical validation. These findings offer insight for curriculum development in Islamic educational institutions, especially in designing programs that promote innovation alongside ethical integrity. Future research should broaden the sample scope and explore deeper pedagogical mechanisms that link Islamic values to entrepreneurial creativity.